Analysis of The Competitiveness ot Green Economy -Based Msmes in The E-Commerce Market for Consumer Millennials in Pidie Regency - Fahkrurrazi Fahkrurrazi; Cut Italina; Nofiana S; Ery Jayanti (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
Study This analyze Power MSME -based competitiveness economy green in the e-commerce market with focus on consumers Millennials in Pidie Regency. Research results show that implementation principle economy green influential positive and significant to Power MSME competitiveness ( coefficient 0.275; p < 0.05) and preference consumer millennials (0.238; p < 0.05). Preferences consumer millennials also have influence significant to Power competitiveness of MSMEs (0.330; p < 0.05). Meanwhile that, digital marketing strategies are proven become the most dominant factor with influence strong direct to Power MSME competitiveness (0.647; p < 0.05) and preference consumer millennials (0.704; p < 0.05). In addition, preferences consumer millennials mediate connection between implementation economy green and digital marketing strategies with Power competitiveness of MSMEs, so that strengthen effect both of them. Research This recommend MSMEs to integrate practice friendly environment like use material standard sustainable and biodegradable packaging, as well as optimize digital marketing through social media, e-commerce, and collaboration with influencers. With Thus, the combination innovation technology and practice business sustainable proven effective in increase Power competitiveness of MSMEs in competitive markets, especially in interesting consumer millennials.